Role of various semiquantitative parameters of 18F-FDG PET/CT studies for interim treatment response evaluation in non-small-cell lung cancer. Issue 10 (October 2017) - Sharma, Akshima; Mohan, Anant; Bhalla, Ashu Seith; Vishnubhatla, Sreenivas; Pandey, Anil Kumar; Bal, Chandra Sekhar; Kumar, Rakesh
Abstract : Purpose: The aim of this study was to prospectively evaluate the role of various semiquantitative parameters obtained from fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET/CT in interim treatment response assessment in biopsy-proven non-small-cell lung cancer (NSCLC) and to find the best parameter, if any. Materials and methods: Totally, 32 patients (male/female: 25/7) with biopsy proven NSCLC and a mean age of 54.71±12.65 years were enrolled in the study. Each patient underwent whole-body 18 F-FDG PET/CT scan after injecting 5.18–7.77 MBq/kg of 18 F-FDG intravenously at baseline and after four cycles of chemotherapy. Five parameters – that is, target-to-background ratio (TBR), maximum standardized uptake value (SUVmax), average standardized uptake value (SUVavg), whole-body metabolic tumor volume (MTVwb), and whole-body total lesion glycolysis (TLGwb) – were evaluated for both scans along with their percentage changes ([INCREMENT]). Patients were divided into two response groups as per Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 criteria: responders and nonresponders. All parameters were compared among the two response groups using appropriate statistical methods; P value of less than 0.05 was considered significant. Results: All postchemotherapy parameters were found to have a significant role in the prediction of two response groups. Post-TBR had highest area under the receiver operating characteristic curve of 0.83 with a sensitivity and specificity of 75 and 82%, respectively, at a cutoff value of 4. The [INCREMENT]s, [INCREMENT]MTVwb, [INCREMENT]TLGwb, and [INCREMENT]SUVmax were significant with cutoffs of −56, −75, and −32%, respectively. [INCREMENT]MTVwb had the highest area under the receiver operating characteristic curve of 0.83 with sensitivity and specificity of 81.25%. In multivariate analysis, post-TBR and [INCREMENT]MTVwb were found to be the independent variables for prediction of interim treatment response. Conclusion: Our study proves that a multitude of semiquantitative parameters as documented above differ significantly between two response groups in patients with advanced stage NSCLC receiving chemotherapy. Moreover, parameters in combination (ΔMTV and post-TBR) with appropriate cutoffs can predict response groups with acceptable reliability.